2019
DOI: 10.3389/fgene.2019.00505
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Deficiency Caused by Castration Modulates Mitochondrial Biogenesis Through the AR/PGC1α/TFAM Pathway

Abstract: Mammalian mitochondrial biogenesis is a complex process involving mitochondrial proliferation and differentiation. Mitochondrial DNA transcription factor A ( TFAM ), which encodes a major component of a protein-mitochondrial DNA (mtDNA) complex, is regulated by peroxisome proliferator-activated receptor γ coactivator 1α (PGC1α). Testosterone is the primary male sex hormone and plays an increasingly important role in mammalian development through its interaction with androgen receptor (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
0
19
1
Order By: Relevance
“…These effects of CPZ on mitochondrial function and thymocyte apoptosis may explain why western blot and flow cytometry analyses of the thymus from CPZ-fed Gi mice identified a reduction in CD4/8 T-cell levels whereas Cx counteracted this effect, at least in part due to the hypertrophy resulting from the ablation of androgens. Supporting this, it has been suggested that androgen depletion may be involved in the regulation of mitochondrial dysfunction and toxic responses (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…These effects of CPZ on mitochondrial function and thymocyte apoptosis may explain why western blot and flow cytometry analyses of the thymus from CPZ-fed Gi mice identified a reduction in CD4/8 T-cell levels whereas Cx counteracted this effect, at least in part due to the hypertrophy resulting from the ablation of androgens. Supporting this, it has been suggested that androgen depletion may be involved in the regulation of mitochondrial dysfunction and toxic responses (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…A correlation between PGC-1α methylation and mtDNA copy number is established with numerous studies reporting that PGC-1α promoter methylation is consistently associated with reduced mRNA expression and lower mtDNA copy numbers in a range of different tissues (Lillycrop et al, 2005;Ling et al, 2008;Barrès et al, 2009;Sookoian et al, 2010;Chen et al, 2012;Gillberg et al, 2014;Heinonen et al, 2015;Kelstrup et al, 2016;Kresovich et al, 2018;Liu et al, 2019;Petrie et al, 2020;Yang et al, 2020). These include studies that focused on both neurological (Yang et al, 2020) and metabolic disorders (Sookoian et al, 2010;Zhao et al, 2017;Kresovich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a rodent model, synergistic activation of two of these markers, namely TFAM and FOXC2, enhanced adipose tissue expression of core proteins of mitochondrial fusion (MFN1, MFN2, and OPA1) consequently leading to a lean and insulin-sensitive phenotype [63][64][65][66]. Noteworthy, given that TFAM, one of the most important mitochondrial DNA transcription factors [67][68][69], contains AR-responsive elements, it is now considered a relevant AR target gene through which testosterone might regulate mitochondrial homeostasis [70]. In line with this evidence, a recent study demonstrated that AR, besides being nuclear, also localizes into mitochondria, where it modulates some of the nongenomic effects of androgens [71].…”
Section: Discussionmentioning
confidence: 99%